Social Work Intervention with Women Offenders: A Pathway to Prevent Recidivism - Mangala Honawar (Asian Social Work Journal, 2019)
Literature has consistently shown that women offenders often have unique needs compared to men primarily due to their role as primary care givers within the family structure. The challenges and needs of women offenders vis-à-vis their vulnerabilities, biases against them, discriminations at various levels and of various kinds in the society and several such factors demand both a professional and a holistic approach towards preventing recidivism among them. Over a period, there has been a growing need for specialized interventions for various populations of people in conflict with law. For example, there is a growing area of intervention for specific categories such as juvenile offenders, young offenders, etc. The statistics on crime show an increasing involvement of women in crime and an emerging need to deal with the issue differently than the existing approach of the Criminal Justice System. It is in this context that professional social workers have an important role to play in prison settings, particularly in the context of women, their vulnerabilities and their involvement in crime. They can intervene during crucial phases such as when the women enter the prison for the first time, during their under-trial detention, conviction period and also provide family related services, health and mental health support and counseling, educational support, facilitate skill development, and job placement in addition to monitoring prison conditions. Social work intervention holds the potential to prevent recidivism among women offenders.